Adhesion and differentiation of Saos-2 osteoblast-like cells on chromium-doped diamond-like carbon coatings - Filova, Elena; Vandrovcova, Marta; Jelinek, Miroslav; Zemek, Josef; Houdkova, Jana; Jan Remsa; Kocourek, Tomas; Stankova, Lubica; Bacakova, Lucie (Journal of materials science. Materials in medicine, 2017)
Diamond-like carbon (DLC) thin films are promising for use in coating orthopaedic, dental and cardiovascular implants. The problem of DLC layers lies in their weak layer adhesion to metal implants. Chromium is used as a dopant for improving the adhesion of DLC films. Cr-DLC layers were prepared by a hybrid technology, using a combination of pulsed laser deposition (PLD) from a graphite target and magnetron sputtering. Depending on the deposition conditions, the concentration of Cr in the DLC layers moved from zero to 10.0 at.%. The effect of DLC layers with 0.0, 0.9, 1.8, 7.3, 7.7 and 10.0 at.% Cr content on the adhesion and osteogenic differentiation of human osteoblast-like Saos-2 cells was assessed in vitro. The DLC samples that contained 7.7 and 10.0 at.% of Cr supported cell spreading on day 1 after seeding. On day three after seeding, the most apparent vinculin-containing focal adhesion plaques were also found on samples with higher concentrations of chromium. On the other hand, the expression of type I collagen and alkaline phosphatase at the mRNA and protein level was the highest on Cr-DLC samples with a lower concentration of Cr (0-1.8 at.%). We can conclude that higher concentrations of chromium supported cell adhesion; however DLC and DLC doped with a lower concentration of chromium supported osteogenic cell differentiation.
Keywords: buněčná diferenciace; Chromium; kovy; osteogeneze; Osteogenesis; Lasers; buněčné linie; alkalická fosfatasa; kolagen typu I; Gene Expression Profiling; osteoblasty; uhlík; Humans; Cell Adhesion; Carbon; Alkaline Phosphatase; talin; Focal Adhesions; Cell Line; Cell Differentiation; Diamond; vinkulin; lasery; buněčná adheze; lidé; fokální adheze; diamant; povrchové vlastnosti; RNA, Messenger; Coated Materials, Biocompatible; Collagen Type I; messenger RNA; Talin; Vinculin; Osteoblasts; chrom; biokompatibilní potahované materiály; Surface Properties; stanovení celkové genové exprese; Metals